2017
DOI: 10.1098/rspb.2017.1901
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural response of migrating humpback whales to a full seismic airgun array

Abstract: Despite concerns on the effects of noise from seismic survey airguns on marine organisms, there remains uncertainty as to the biological significance of any response. This study quantifies and interprets the response of migrating humpback whales () to a 3130 in (51.3l) commercial airgun array. We compare the behavioural responses to trials (array operational; = 34 whale groups), with responses to trials (source vessel towing the array while silent; = 33) and studies of normal behaviour in the absence of the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…The effect of anthropogenic noise on animals [15,[111][112][113][114]] is a key topic in bioacoustics research. Noise is usually the result of the sound of vehicles and has been shown to have a negative effect on animal foraging [113].…”
Section: Anthropogenic Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The effect of anthropogenic noise on animals [15,[111][112][113][114]] is a key topic in bioacoustics research. Noise is usually the result of the sound of vehicles and has been shown to have a negative effect on animal foraging [113].…”
Section: Anthropogenic Noisementioning
confidence: 99%
“…In ecology, the automated analysis of animal sounds can be used for individual animal detection [6], species detection [7,8], location of animal detection [9][10][11] and population monitoring [6,12 -14]. In conservation, it is useful when verifying if human activities such as shipping or seismic survey vessels affect wild animal behaviour [15][16][17][18][19]. Vocalizations of some species such as goats (Capra hircus) and horses (Equus caballus) also differ during positive and negative experiences [20 -23].…”
Section: Introductionmentioning
confidence: 99%
“…The physical presence of the vessel has been shown to reduce bottlenose dolphin [37] and humpback whale [38] foraging activity as well as bottlenose dolphin resting and socializing behaviour [37]. Other studies, carried out on this population of humpback whales at this study site, found that humpback whale groups significantly changed their migration speed and direction to avoid a slowly (4 knots) moving vessel towing (silent) air gun arrays [39,40]. Therefore, this body of work suggests that not only do migrating humpback whales physically avoid vessels, but also change their acoustic and social behaviour when vessels are present.…”
Section: Discussionmentioning
confidence: 97%
“…Humpback whales off the Australian east coast exhibited great variation in behavioral responses to seismic survey vessels with the airguns turned off. While no behavioral change was seen in some trials, others revealed a decrease in dive duration, travel speed, and the number of breaches (Dunlop et al, 2015(Dunlop et al, , 2016(Dunlop et al, , 2017a(Dunlop et al, ,b, 2018. Most humpback whales did not respond to sonar vessels with the sonar turned off Wensveen et al, 2017).…”
Section: Mysticetesmentioning
confidence: 99%